Expropriação camponesa, agronegócio e precarização do trabalho em Livramento de Nossa Senhora (BA) - Dourado, José Aparecido Lima; de Mesquita, Helena Angélica (Universidade Federal Rural do Rio de Janeiro, 2015)
It is our intention with this article make some reflections on the process of precarious work in the field and in the city, from the insertion of the municipality of Livramento de Nossa Senhora (BA) in the circuits of capitalist modernization. Since the implementation of the irrigation project in the city in the second half of the 1980s, the local agricultural area is undergoing sweeping changes due to its incorporation into the logic of big business that, through the new territorial division of labor, are assigned "roles anomalous" livramentense for agriculture. With the expansion of cultivation of mango, verify the reduction of areas occupied by oriented crops for domestic consumption as well as changes in labor relations in the field, there is therefore the need to contextualize this phenomenon with the changes that are going on in the world work from the 70s of the twentieth century, due to the restructuring of productive capital. The data presented in this article are the results of literature search and field work as an attempt to interpret reality searched from the dialogue between theory and empiricism.